2020
DOI: 10.1002/jctb.6523
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐light driven photodegradation of phenol over niobium oxide‐loaded fibrous silica titania composite catalyst

Abstract: BACKGROUND Heterogeneous photocatalysis has been demonstrated to be a promising alternative to treating emerging pollutants in wastewater. Phenol, an extremely toxic substance among existing pollutants, can cause long‐term unintended effects when improperly disposed. An effective measure to address this problem is to develop suitable heterojunctions. Among various photocatalyst, titanium dioxide (TiO2) appears to be an excellent photocatalyst in the degradation of organic pollutants. RESULTS Synthetization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Consequently, activation of TiO 2 nanoparticles by the UV-light produced reactive species (OH), which facilitated the degradation of organics in the solution [ 12 , 33 ]. As shown in Figure 3 b, the degradability followed the first-order kinetics for irradiation time less than 60 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, activation of TiO 2 nanoparticles by the UV-light produced reactive species (OH), which facilitated the degradation of organics in the solution [ 12 , 33 ]. As shown in Figure 3 b, the degradability followed the first-order kinetics for irradiation time less than 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…The positive sign represents the synergistic effect of the term on the response, whereas, the negative sign points out an antagonistic effect. In this view, the increasing order of the effect of the terms for the removal of colour follows AC > B 2 > AB > B > A > C, whereas that of the turbidity removal is AC > AB > B > C 2 > A > C. Also, the optimal values of the parameters are obtained by estimating the regression equation and the analysis of the surface response: Consequently, activation of TiO 2 nanoparticles by the UV-light produced reactive species (OH), which facilitated the degradation of organics in the solution [12,33]. As shown in Figure 3b, the degradability followed the first-order kinetics for irradiation time less than 60 min.…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Notwithstanding, the dominating phase of the TiO 2 pattern in all the samples by the XRD peaks ( Figure 1) within the angle range of 2θ (5 • > 2θ > 70 • ) is anatase corresponding to the JCPDS Files No.21-1272 [33,34]. The peaks observed at 2θ values of 25 (Figure 1) by the broad bump of A-TiO 2 around 2θ = 25.28 • . Adding to this, the reflection peak in the A-TiO 2 of the anatase around 2θ = 25.67 • decreased, whereas the rutile peak at 2θ = 27.45 • (002) became sharper and stronger.…”
Section: Introductionmentioning
confidence: 86%
“…9 Meanwhile, its photogenerated carriers are easy to recombine, reducing the photocatalytic performance. 10,11 Constructing heterojunctions could effectively constrain the recombination of carriers, boosting the photocatalytic performance of Bi 4 O 5 Br 2 by combining with another semiconductor (such as BiOBr, AgBr, g-C 3 N 4 , etc.). 12 For example, Chen et al reported that the AgBr/Bi 4 O 5 Br 2 Z-scheme heterojunction was prepared by hydrothermal combination and ion exchange method for nitrogen fixation reaction, which greatly suppressed the recombination of photo-generated carriers.…”
Section: Introductionmentioning
confidence: 99%